Comparative efficacy of 20 graft-versus-host disease prophylaxis therapies for patients after hematopoietic stem-cell transplantation: A multiple-treatments network meta-analysis. (June 2020) - Lv, Xin; Qi, Jiaqian; Zhou, Meng; Shi, Bingyu; Cai, Chengsen; Tang, Yaqiong; Pan, Tingting; Han, Yue
Abstract: Background: Graft-versus-host disease (GVHD) is a leading cause of death in patients after hematopoietic stem-cell transplantation (HSCT). Previous studies have shown different efficacy of GVHD prophylaxis therapies. Methods: We reviewed 46 randomized controlled trials (including 8050 participants) systematically from Jun 20, 2004 to Aug 20, 2019. These investigations compared the following drugs or their combination at therapeutic dose range for GVHD after HSCT. The main results were based on the proportion of patients who respond to these therapies. Results: Cyclosporine + methotrexate + Anti-T cell globulin (ATG), tacrolimus + methotrexate + ATG, tacrolimus + bortezomib + sirolimus and cyclosporine + marrow mesenchymal stem cells (MMSCs) were significantly more efficacious than corticosteroids alone (OR: 12.15, 6.71, 6.25, 3.73). corticosteroids alone were less efficacious than all the other GVHD prophylaxis therapies tested. Conclusion: Cyclosporine + methotrexate + ATG may be the best choice when starting treatment for GVHD.